The Association Between Changes in the University Educational Setting and Peer Relationships: Effects in Students' Depressive Symptoms During the COVID-19 Pandemic - Conceição, Virgínia; Rothes, Inês; Gusmão, Ricardo (Frontiers in Psychiatry, 2021)
Objective: Abrupt life changes imposed by the lockdown measures, with a direct impact on teaching methodology and social interactions, as well as sleeping patterns, harmed university student’s mental health. This study aimed to analyze the relationship between satisfaction with online teaching, social interaction with depression, and anxiety symptomatology, as well as help-seeking behaviours. Methods: The survey collected information on demographic data, satisfaction with online teaching, and social interaction. We evaluated the depression and anxiety symptomatology using the 9-item Patient Health Questionnaire and the 7-item Generalized Anxiety Disorder, respectively. We used the cut-off 15 of the PHQ-9 for moderately severe depressive symptoms and the cut-off 10 of the GAD-7 for moderately severe anxiety symptoms. This study used three data points: October 2019, June 2020, and March 2021. Findings: The study included 366 participants from all university study fields, with a mean age of 21.71 (SD=1.42) in the last evaluation, and 71.3% were women. Depressive symptoms significantly increased from October 2019 to June 2020, and the mean scores kept growing until March 2021. Anxiety symptoms also significantly increased from October 2019 to June 2020; however, from June 2020 to March 2021, there was a non-significant decrease in the proportion. Mean scores for satisfaction with online teaching were 38.23% in June 2020 and 34.25% in March 2021, a non-significant difference. Satisfaction with social interaction significantly decreased from 37.35% in 2020 to 24.41% in 2021. Participants with scores above the cut-off of moderately severe and severe depressive and anxiety symptoms showed significantly lower satisfaction with online teaching than students with better scores in the depression and anxiety scales. Despite the significant increase on clinical symptomatology, help-seeking behaviours did not change accordingly, and more than 50% of the students with mild or severe depressive and/or anxiety symptomatology did not get treatment during the pandemic. Conclusion: The findings of this study suggest that most students are dissatisfied with online teaching and with the type of social interaction they were forced to adopt because of the pandemic. The severity of depressive and anxiety symptomatology significantly increased, but help-seeking behaviours did not increase accordingly.